Influence of Religious Culture, Tourism Revitalization, Visitor Interest, and BUMDES Empowerment to Welfare of Business Operators in Benowo Park Tourism - Fitri Mukarromah; Nur Ilyas Subakti; Amalliyah Amalliyah (UIN Siber Syekh Nurjati Cirebon, 2023)
Â Abstract Since the pandemic and the enactment of various regulations ranging from PSBB to PPKM, a number of tourist attractions are not operating. This has an impact on the tourism industry and the welfare of business actors in various tourism. This research is a type of quantitative research. The data collection method in this study was a questionnaire method using a sample of 45 respondents. Sampling technique with saturated sample method. This study uses the method of data analysis multiple linear regression test with the help of SPSS 25. The results of the study show that partially the revitalization of religious cultural tourism has no effect on the welfare of business actors. Meanwhile, mountaineers' interest and BUMDes empowerment affect the welfare of business actors. Then simultaneously, tourism revitalization, visitor interest, and BUMDes empowerment affect the welfare of business actors.Keywords: Tourism Revitalization, Visitor Interest, BUMDes EmpowermentÂ AbstrakSejak adanya pandemi dan diberlakukannya berbagai aturan mulai dari PSBB hingga PPKM sejumlah tempat wisata tidak beroperasi. Hal tersebut berdampak pada industri pariwisata dan kesejahteraan pelaku usaha diberbagai pariwisata. Penelitian ini termasuk jenis penelitian kuantitatif. Metode pengumpulan data dalam penelitian ini adalah metode kuesioner dengan menggunakan sampel sebanyak 45 responden. Teknik pengambilan sampel dengan metode sampel jenuh. Penelitian ini menggunakan metode analisis data uji regresi linier berganda dengan bantuan SPSS 25. Hasil penelitian menunjukkan bahwa secara parsial revitalisasi pariwisata budaya religi tidak berpengaruh terhadap kesejahteraan pelaku usaha. Sedangkan minat pengunung dan pemberdayaan BUMDes berpengaruh terhadap kesejahteraan pelaku usaha. Kemudian secara simultan, revitalisasi pariwisata, minat pengunjung, dan pemberdayaa BUMDes berpengaruh terhadap kesejahteraan pelaku usaha.Kata kunci: Revitalisasi Pariwisata, Minat Pengunjung, Pemberdayaan BUMDes.